From recognition to cause: analyzing parental knowledge of children's short stature, preliminary study - Mariam S. Alharbi (Springer, 2024)
Abstract Short stature (SS) is a condition where children's growth rates are below the 2.5th percentile for their age and gender. Early intervention is vital due to its association with reduced quality of life and mortality. This study examines the understanding of Qassimi parents regarding their child's SS. We surveyed 384 Qassimi parents, including those with growing children and those without children willing to participate. Knowledge scores ranged from 0 to 8, with scores over 4 indicating good knowledge. Most of the study participants were Saudis, females, or holding a university degree. The mean score was 4.44 and almost 47% of respondents demonstrated good knowledge. All the study participants were aware of at least one cause of short stature. Of more than 20 causes of short stature, only 24.3% of the study participants could correctly identify 4 or more causes. Multivariable regression revealed that higher knowledge scores were significantly noted among participants younger than 40 years (p-value: < 0.001), students (p-value: < 0.001), unmarried (p-value: 0.001), and/or having no children (p-values: 0.001). Among respondents with children, individuals with children younger than 12 years had significantly better knowledge (p-value: 0.003). In contrast, knowledge was seemingly independent of gender, level of education, nationality, or family history (p-values: > 0.05). Although the knowledge status is overall moderate, it's recommended to further start public health initiatives and educational programs, while paying special attention to population groups associated with lower knowledge level.